The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5194/essd-13-4275-2021
|View full text |Cite
|
Sign up to set email alerts
|

UV-Indien network: ground-based measurements dedicated to the monitoring of UV radiation over the western Indian Ocean

Abstract: Abstract. Within the framework of the UV-Indien network, nine ground stations have been equipped with ultraviolet broadband radiometers, five of them have also been equipped with an all-sky camera, and the main station in Saint-Denis de la Réunion is also equipped with a spectroradiometer. These stations are spatially distributed to cover a wide range of latitudes, longitudes, altitudes, and environmental conditions in five countries of the western Indian Ocean region (Comoros, France, Madagascar, Mauritius, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
2
4
0
2
Order By: Relevance
“…A maximum happening in months of transition to the dry period the rainy (December-January) was also reported by [4,38] in their studies of UVI variability at tropical latitudes. [4] found comparable characteristics by studying the variability of UVI at Indian Ocean stations located at different latitudes between the equator and 20° S. For example, they observed that Mahé, at 4.6° S, had a higher mean UVI than the cities more at the south and explained that the difference was due to latitude. Santarém is located in a tropical region, at a low latitude, close to the equator, therefore solar zenith angle (SZA) is lower throughout the year, which induces a higher UVR, smaller amplitude between the seasons, as well as a very low photoperiod variation.…”
Section: Uvr Hour-daily Series In Clear Sky and All Sky Conditionssupporting
confidence: 70%
See 2 more Smart Citations
“…A maximum happening in months of transition to the dry period the rainy (December-January) was also reported by [4,38] in their studies of UVI variability at tropical latitudes. [4] found comparable characteristics by studying the variability of UVI at Indian Ocean stations located at different latitudes between the equator and 20° S. For example, they observed that Mahé, at 4.6° S, had a higher mean UVI than the cities more at the south and explained that the difference was due to latitude. Santarém is located in a tropical region, at a low latitude, close to the equator, therefore solar zenith angle (SZA) is lower throughout the year, which induces a higher UVR, smaller amplitude between the seasons, as well as a very low photoperiod variation.…”
Section: Uvr Hour-daily Series In Clear Sky and All Sky Conditionssupporting
confidence: 70%
“…A maximum happening in months of transition to the dry period the rainy (December-January) was also reported by [4,38] in their studies of UVI variability at tropical latitudes. [4] found comparable characteristics by studying the variability of UVI at Indian Ocean stations located at different latitudes between the equator and 20 • S. For example, they observed that Mahé, at 4.6 • S, had a higher mean UVI than the cities more at the south and explained that the difference was due to latitude.…”
Section: Uvr Hour-daily Series In Clear Sky and All Sky Conditionssupporting
confidence: 70%
See 1 more Smart Citation
“…The manufacturer offers a calibration accounting for the solar zenith angle and the total ozone column. Between each vessel rotation, the radiometers undergo recalibration at the Saint-Denis UV station, a part of the UV-Indien network (Lamy et al, 2021a), in Reunion Island. This process involves comparing the radiometers' readings with the calibrated values of a Bentham DTMc300 spectroradiometer (https://www.bentham.co.uk/products/components/ dtmc300-double-monochromator-39, last access: 8 November 2023).…”
Section: Uv Solar Radiationmentioning
confidence: 99%
“…(17,18,59,60) Solar UVR consists of electromagnetic wavelengths between 100 and 400 nm that reach the terrestrial surface and has a direct effect on human health and terrestrial and aquatic ecosystems, as well as material degradation. (61)(62)(63)(64) It is divided into three components, depending on its transmission capability in the atmosphere and its biological effects: UVA (315-400 nm) makes up most of the UVR received on the terrestrial surface; UVB (280-315 nm) which is partially absorbed into the atmosphere, and UVC (100-280 nm) which is completely absorbed by stratospheric ozone. (34,64) Both UVA and UVB wavelengths have been shown to contribute to photoaging, by imbalanced ROS/ RNS production and/or by direct DNA damage.…”
Section: Melatonin and Uv Protectionmentioning
confidence: 99%